The long‐term impact of magnesium in seawater on foraminiferal mineralogy: Mechanism and consequences. Issue 3 (8th March 2016) - van Dijk, I.; de Nooijer, L. J.; Hart, M. B.; Reichart, G.‐J.
Abstract: Foraminifera are unicellular protists, primarily known for their calcium carbonate shells that provide an extensive fossil record. This record, ranging from Cambrian to present shows both major shifts and gradual changes in the relative occurrence of taxa producing different polymorphs of carbonate. Here we present evidence for coupling between shifts in calcite‐ versus aragonite‐producing species and periods with, respectively, low and high seawater Mg/Ca throughout the Phanerozoic. During periods when seawater Mg/Ca is <2 mol/mol, low‐Mg calcite‐producing species dominate the foraminiferal community. Vice versa, high‐Mg calcite‐ and aragonite‐producing species are more abundant during periods with relatively high seawater Mg/Ca. This alteration in dominance of the phase precipitated is due to selective recovery of groups producing the favorable polymorph after shifts from calcite to aragonite seas. In addition, relatively high extinction rates of species producing the mineral phase not favored by the seawater Mg/Ca of that time may be responsible for this alteration. These results imply that the current high seawater Mg/Ca will, in the long term, favor prevalence of high‐Mg and aragonite‐producing foraminifera over calcite‐producing taxa, possibly shifting the balance toward a community in which calcite production is less dominant. Key Points: Long‐term trends in fossil foraminiferal species are in line with fluctuations in Mg/Casw Foraminifera producing a favored biomineral are more likely to recovery after extinction events Currently, all low‐Mg calcite‐producing foraminifera calcify in unfavorable seawater Mg/Ca